1991
DOI: 10.1002/ijc.2910470528
|View full text |Cite
|
Sign up to set email alerts
|

Biological response of multicellular emt6 spheroids to exogenous lactate

Abstract: The influence of elevated lactate concentrations, as found in tumor microregions, on cellular growth, viability, and metabolic state was studied employing the multicellular spheroid model. Spheroids of EMT6/Ro cells were cultured at 37 degrees C in 5% or 20% (v/v) oxygen, using stirred media with various concentrations of exogenous lactate ranging from 0.0 mM (standard conditions) to 20.0 mM. Elevated concentrations of exogenous lactate led to a considerable decrease of the maximum spheroid diameter at growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 26 publications
4
31
0
Order By: Relevance
“…Fig. S1) showed a similar growth behavior to that described for human carcinoma HepG2, human glioblastoma SNB19, mouse mammary EMT6 spheroids (Bourrat-Floeck et al, 1991;Hauptmann et al, 1998;Kelm et al, 2003), and T47-D and Hek293 spheroids (Gallardo-Pérez JC and Maldonado V, unpublished work). In all these models the maximal diameters reached were around 1 mm.…”
Section: Morphology and Growth Of Mctssupporting
confidence: 67%
“…Fig. S1) showed a similar growth behavior to that described for human carcinoma HepG2, human glioblastoma SNB19, mouse mammary EMT6 spheroids (Bourrat-Floeck et al, 1991;Hauptmann et al, 1998;Kelm et al, 2003), and T47-D and Hek293 spheroids (Gallardo-Pérez JC and Maldonado V, unpublished work). In all these models the maximal diameters reached were around 1 mm.…”
Section: Morphology and Growth Of Mctssupporting
confidence: 67%
“…The interactions observed between these nutrients suggested that EMT6 cells in spheroids can adapt their metabolic rates substantially to different supply conditions (Mueller-Klieser et al 1986). as well as to the concentration of lactate (Bourrat-Floeck et al 1991). On this basis.…”
Section: Resultsmentioning
confidence: 85%
“…Similar proliferation-related changes occur in spheroids with a decrease in the overall oxygen uptake of spheroids during the cultivation period (Freyer et al, 1984;Freyer and Sutherland, 1985;Mueller-Klieser et al, 1986a;Bourrat-Floeck et al, 1991). In contrast, the respiratory activity within these spheroids seems to be rather uniform despite a nonuniform distribution of proliferating and quiescent cells (Mueller-Klieser, 1984;MuellerKlieser et al, 1986a;Bourrat-Floeck et al, 1991).…”
mentioning
confidence: 88%
“…The former parameter resulted in a mean value ( 5 SEM) of (3.8 ? 0.25) x m10,/cm3/s for EMTG spheroids with necrosis in a n experimental series published elsewhere (Bourrat-Floeck et al, 1991). An autoradiographic picture and the thymidine labeling index LI a t various depths into the spheroid is shown in a and b, respectively, of Figure 5.…”
Section: Multicellular Emtg Spheroidsmentioning
confidence: 98%